Isoniazid preventative therapy uptake for child household contacts of TB index cases, Kisumu County, Kenya, 2014-2015 - Barbara Burmen; Kennedy Mutai; Timothy Malika (AOSIS, 2018)
Background Isoniazid Preventative Therapy (IPT) is recommended for children aged less than 5 years that have been in contact with an open case of TB and screen negative for TB to prevent the risk of TB progression. We examined IPT uptake among child household contacts of TB index cases within a TB case detection study in a high TB burden region. Methods A cross-sectional study involving all IPT eligible children drawn from a TB case detection study was done in Kisumu County, Kenya between 2014 and 2015. By linking a subset study database to the TB program IPT register, we described Child contacts as 'initiated on IPT' and TB index cases as 'having child contacts initiated on IPT' based on whether their names or their child contacts names respectively, were found in the IPT register. Logistic regression analysis was used to describe index and contact characteristics associated with IPT initiation Results Of 555 TB index cases into the study, 243 (44%) had a total of 337 IPT-eligible child household contacts. Forty-seven (19%) index cases that had child contacts initiated on IPT; they were more likely to have been diagnosed with smear positive TB compared to those who were diagnosed with smear negative TB (OR 5.1, 95% CI 1.1-23.2; p=0.03) and to reside in rural Kisumu compared to those in urban Kisumu (OR 3.3, 05% CI 1.6-6.8; p<0.01). The 51 (15%) child contacts that were initiated on IPT were more likely to be were first degree relatives of the index case compared to those who were not (OR 2.6, 95% CI 1.2-5.5; p=0.02) and to reside in rural Kisumu compared to those in urban Kisumu (OR 2.6, 95% CI 1.2-5.1; p<0.01). Conclusion IPT initiation, which is influenced by index and contact characteristics, is suboptimal. The TB program should provide health worker training, avail appropriate pediatric TB diagnostic tools and continuous supply of medication, and job aids and monitoring tools to facilitate IPT implementation. Additionally, targeted health education interventions should be formulated to reach those who are unlikely to accept IPT.